Socio-demographic and clinical profile of patients visiting the emergency department of Karnali Academy of Health Sciences - Gautam, Sundar; Bhandari, Jeetendra; Mahat, Pradeep; Tamrakar, Prashamsha; Pradhan, Anuradha (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Emergency departments (ED) are essential access points for immediate medical care, especially in resource-limited settings. Karnali Province, Nepal, is one of the most geographically isolated and socioeconomically disadvantaged regions, where delivering healthcare is hindered by challenging terrain and inadequate resources. The Emergency Department of the Karnali Academy of Health Sciences acts as the primary tertiary care center for this underserved population. This study aimed to analyze the sociodemographic and clinical profiles of patients visiting the ED at KAHS to guide healthcare planning and resource allocation.Method: A retrospective cross-sectional study utilized medical records from emergency department visits at KAHS from Shrawn 2080 to Ashad 2081 (July 2023–June 2024). Data regarding sociodemographic characteristics, diagnoses, admission status, and discharge types were collected and analyzed through SPSS version 20. Result: In total, 11,666 patients attended the ED over the period of one year. The average age was 34.92±21.16 years, with a male-to-female ratio of 1.07:1. The majority of patients were from Chandannath Municipality 3201(27.44%). The most frequently observed conditions were respiratory system diseases 3254(27.89%) and infectious diseases 2619(22.45%). Among all patients, 2979(25.54%) required hospitalization, 1126(37.79%) in internal medicine and 663(22.26%) in surgery (22.26%). Seasonal patterns showed an increase in admissions during the warm seasons.Conclusion: This research reveals substantial socio-demographic differences and disease burdens in Karnali Province, stressing the importance of targeted measures like mobile health units, preventive initiatives for respiratory and infectious diseases, and enhanced access to specialists. These insights can inform healthcare policy formulation in remote areas.